Integration of Therapeutic Communication Practices by Caregivers, Healthcare Workers, and Village Health Workers with Patients in the Process of Mental Health Recovery - Indyana Ummi Aisyah; Sri Wahyuningsih (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to examine the application of therapeutic communication by caregivers to patients in the recovery process of mental health disorders in Blumbungan Village, Pamekasan. The method used is a qualitative approach with a phenomenological design through in-depth interviews with health workers, village cadres, and patients’ families. The results of the study indicate that therapeutic communication has been implemented through the Posyandu Jiwa program, home visits, and family psychoeducation. The implementation process faces various obstacles, such as patient resistance, family stigma, low mental health literacy, and limited access to therapeutic treatment. Caregivers play a crucial role in providing emotional support, education, and treatment supervision, but still require increased capacity and support from the health system. Consistently applied therapeutic communication can help reduce patients’ anxiety levels and support the gradual process of mental health recovery. These findings underscore the importance of integrating medical and cultural strategies in community-based mental health services, as well as the need to strengthen therapeutic communication skills among caregivers to enhance the effectiveness of patient recovery. The results also indicate that empathetic communication, patience, and family involvement contribute to the stability of patients with mental health disorders. This process unfolds through the stages of orientation, identification, exploration, and resolution, and is reinforced by social support and access to health services.